2020
DOI: 10.1002/jmv.26450
|View full text |Cite
|
Sign up to set email alerts
|

Convergence between global BCG vaccination and COVID‐19 pandemic

Abstract: The novel coronavirus SARS‐CoV‐2 has kept the whole world in tenterhooks due to its severe life‐threatening infectious disease, COVID‐19. The virus is distinct its cousins, SARS‐CoV and MERS‐CoV in term of severity of the infection. The obligated killing properties of the SARS‐CoV‐2 virus is mediated by its unique structure. Efforts for developing vaccines for COVID‐19 are ongoing, but it is unlikely to be available in the immediate future. Due to the absence of precise treatment, the investigators are discove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Escobar et al performed an epidemiological study, after eliminating the potential confounding factors such as the COVID-19 epidemic stages, geographical distribution, population density, and age structure, they found a 10% increase in the BCG index resulted in a 10.4% decrease in COVID-19 deaths [88] . Interestingly, a large number of subsequent ecological studies have found a similar phenomenon that BCG vaccination rates and years of implementation of the BCG vaccination policy are significantly negatively correlated with COVID-19 morbidity and mortality [14] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] , [101] , [102] , [103] , [104] , [105] , [106] , [107] , [108] , [109] , [110] , [111] , [112] , [113] .…”
Section: Is the Bcg Vaccine Effective Against Sars-cov-2 Infection?mentioning
confidence: 88%
“…Escobar et al performed an epidemiological study, after eliminating the potential confounding factors such as the COVID-19 epidemic stages, geographical distribution, population density, and age structure, they found a 10% increase in the BCG index resulted in a 10.4% decrease in COVID-19 deaths [88] . Interestingly, a large number of subsequent ecological studies have found a similar phenomenon that BCG vaccination rates and years of implementation of the BCG vaccination policy are significantly negatively correlated with COVID-19 morbidity and mortality [14] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] , [101] , [102] , [103] , [104] , [105] , [106] , [107] , [108] , [109] , [110] , [111] , [112] , [113] .…”
Section: Is the Bcg Vaccine Effective Against Sars-cov-2 Infection?mentioning
confidence: 88%
“…In addition, the developed solution utilizes recent data for enhancing CT images diagnosis and detection accuracy. Remarkable applications of emerging technologies used to defeat COVID-19 are discussed in the upcoming subsection [169][170][171].…”
Section: Leveraging Technologies For Covid-19 and Future Pandemicsmentioning
confidence: 99%
“…9 The same may apply to studies that are using disparate data sets from a later stage of the COVID-19 pandemic and conclude the vaccinated countries to be more protected while overlooking the presence of countries with minimal COVID-19 effect in no BCG vaccination policy countries as well. 10 Similarly, the studies trying to correlate childhood BCG vaccination to higher COVID-19 incidence or as a risk factor are also potentially indefensible due to gross overlooking of the basic facts about the longevity of trained…”
Section: Introductionmentioning
confidence: 99%